A cobalt oxyhydroxide-modified upconversion nanosystem for sensitive fluorescence sensing of ascorbic acid in human plasma. Issue 33 (29th July 2015) - Cen, Yao; Tang, Jun; Kong, Xiang-Juan; Wu, Shuang; Yuan, Jing; Yu, Ru-Qin; Chu, Xia
Abstract : A novel cobalt oxyhydroxide (CoOOH) nanoflakes modified upconversion nanosystem was constructed for the sensitive and selective determination of ascorbic acid in human plasma based on FRET from upconversion nanoparticles (UCNPs) to CoOOH nanoflakes. Abstract : Ascorbic acid (AA), a potent antioxidant readily scavenging reactive species, is a crucial micronutrient involved in many biochemical processes. Here, we have developed a cobalt oxyhydroxide (CoOOH)-modified upconversion nanosystem for fluorescence sensing of AA activity in human plasma. The nanosystem consists of upconversion nanoparticles (UCNPs) NaYF4 :30% Yb, 0.5% Tm@NaYF4, which serve as energy donors, and CoOOH nanoflakes formed on the surface of UCNPs, which act as efficient energy acceptors. The fluorescence resonance energy transfer (FRET) process from the UCNPs to the absorbance of the CoOOH nanoflakes occurs in the nanosystem. The AA-mediated specific redox reaction reduces CoOOH into Co 2+, leading to the inhibition of FRET, and resulting in the recovery of upconversion emission spectra. On the basis of these features, the nanosystem can be used for sensing AA activity with sensitivity and selectivity. Moreover, due to the minimizing background interference provided by UCNPs, the nanosystem has been applied to monitoring AA levels in human plasma sample with satisfactory results. The proposed approach may potentially provide an analytical platform for research and clinical diagnosis of AA related diseases.